A pragmatic randomised controlled trial of the fostering changes programme. (October 2020) - Moody, Gwenllian; Coulman, Elinor; Brookes-Howell, Lucy; Cannings-John, Rebecca; Channon, Susan; Lau, Mandy; Rees, Alyson; Segrott, Jeremy; Scourfield, Jonathan; Robling, Michael
Abstract: Background: Many looked after young people in Wales are cared for by foster or kinship carers, usually as a consequence of maltreatment or developmentally traumatising experiences within a family context. Confidence in Care is a pragmatic unblinded individually randomised controlled parallel group trial evaluating a training programme to improve foster carer self-efficacy, when compared to usual care. Objective: To determine whether group-based training improves foster carer self-efficacy. Participants and setting: Participants are foster carers, currently looking after children aged 2+ years for at least 12 weeks. Carers from households where one or more carer had previously attended the training were not eligible. Sixteen local authorities and three independent fostering providers in Wales took part. Methods: The primary outcome measure was the Carer Efficacy Questionnaire assessed at 12 months. Secondary outcomes included the Strengths and Difficulties Questionnaire, Quality of Attachment Questionnaire, Carer Defined Problems Scale, Carer Coping Strategies, placement moves. Results: 312 consented foster carers were allocated to FC (n = 204) or usual care (n = 108) group. 65.3 % of FC group participants attended sufficient training sessions (8/12, including sessions three and four). There were no differences in carer-reported self-efficacy at 12 months (adjusted difference in means (95 % CI): -0.19 (-1.38 to 1.00)). Small differences in carer-reported child behaviour difficulties and carer coping strategies over time favoured the intervention but these effects diminished from three to 12 months. No other intervention effects were observed. Conclusions: Although well-received by participants, training was associated with small and mostly short-term benefit for trial secondary outcomes.